The effect of potassium on the yield and concentrations of microelements in cowpea (Vigna unguiculata L. Walp.) under drought stress - seyed morteza zahedi; Farzad Rasoli; Gholamreza Gohari (فیزیولوژی محیطی گیاهی, 2017)
In order to study the effect of drought stress and application of potassium on seed yield, some biochemical characteristics, and the content of micronutrients such as copper (Cu), zinc (Zn) and manganese (Mn) in cowpea, a factorial experiment was carried out in randomized complete block design with three replications in the greenhouse of the Faculty of Agriculture, University of Maragheh, Iran in 2016. Treatments were water stress at two levels (normal or 100% and 50% field capacity) as the first factor and potassium at five levels (0, 30, 60, 90, and 120 mg/kg) as the second factor. Results showed that drought stress reduced the growth parameters and the concentration of the elements in plants while application of different levels of potassium increased shoot dry weight, yield, and carbohydrate by adjusting the effects of drought stress. Also, application of 120 mg potassium in stress conditions caused an increase in the concentration of Cu, Zn and, Mn. Findings seem to suggest that potassium improves growth characteristics in cowpea by decreasing the undesirable consequences of drought stress. Therefore, application of potassium sulfate is recommended as a strategy to mitigate the effects of draught stress in cultivation of cowpea.